India : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2003)
This paper discusses the intermediation of financial saving in India and the implications for growth. Recent studies linking financial sector development and growth in India are reviewed. The following statistical data are also provided: employment and labor statistics, agricultural production and yields, index of industrial production, saving and investment, price developments, balance of payments, official reserves, reserve money, monetary survey, central and state government operations, indicators of financial system soundness, financial performance of Indian commercial banks, and selected monetary and exchange rate indicators.